1962
DOI: 10.1099/00221287-29-4-637
|View full text |Cite
|
Sign up to set email alerts
|

The Eventual Intracellular Destruction of Staphylococci by Mononuclear Cells

Abstract: SUMMARYIt was found that Staphylococcus aureus usually survived within monocytes of normal rabbits for several hours without multiplication, but were eventually destroyed. However, there was variation in the intracellular behaviour in leucocytes of different rabbits in that cells from some donors began the slow destruction of the staphylococci shortly after phagocytosis.In many of these experiments streptomycin was incorporated in the tissue-culture medium to suppress the extracellular multiplication of staphy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1962
1962
1978
1978

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…These latter studies were performed using the leucocytes from a single human donor and thus might not reflect a general phenomenon. This view might be supported by the observed variation in the behaviour of staphylococci within leucocytes derived from different rabbits (Shayegani & Kapral, 1962).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…These latter studies were performed using the leucocytes from a single human donor and thus might not reflect a general phenomenon. This view might be supported by the observed variation in the behaviour of staphylococci within leucocytes derived from different rabbits (Shayegani & Kapral, 1962).…”
Section: Discussionsupporting
confidence: 60%
“…In previous publications (Kapral & Shayegani, 1959;Shayegani & Kapral, 1962) the authors reported that Staphylococcus aureus usually survived for several hours within polymorphonuclear leucocytes and monocytes of normal rabbits, but were eventually slowly destroyed within the monocytes. S. albus, however, was rapidly destroyed by these cells under the same conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Administration of the antigens alone seemed to have no effect on host resistance. Since S. aureus do not multiply within the cells (13,14) and are therefore eventually eliminated, the presence of homologous antigens is needed for stimulation of cellular resistance. This finding confirms a previous report (12) describing the need for elicitation in which cell-mediated immunity was tested at the cellular level, using peritoneal macrophages from infected and elicited animals in order to study the intracellular destruction of S. aureus.…”
Section: Resultsmentioning
confidence: 99%
“…In applying the Trudeau experience to staphylococcal infection, it is relevant that Staphylococcus aureus does not multiply in macrophages (18,19).…”
mentioning
confidence: 99%